Avaliação fitoquímica, capacidade antioxidante e fotoprotetora do extrato e formulações de Calendula officinalis L. - Deuschle, Viviane Cecilia Kessler Nunes (2013)
There are many factors related to oxidative stress, one of which is exposure to ultraviolet (UV) radiation, which generates reactive oxygen species (ROS). Calendula officinalis L. presents phenolic compounds, saponins, carotenoids, triterpene alcohols, steroids, terpenoids and triterpenoids. Thus, this work aims to perform a phytochemical evaluation of hydroethanolic extract of calendula, and determine its antioxidant capacity and photoprotection in vitro and in cosmetic formulations developed with this extract. Hydroethanolic extract was obtained by maceration, concentrated in a rotary evaporator and then lyophilized. Phenolics, total flavonoids and condensed tannins were determined spectrophotometrically and the identification and quantification of polyphenols was determined by high performance liquid chromatography (HPLC ). The antioxidant capacity was determined by the DPPH method and SPF determined spectrophotometrically. The antiradical activity was assessed by the hydroxyl radical and superoxide method. Extract was embedded in gel and cream formulations and evaluated for physical and chemical stability during 90 days, where the parameters were the organoleptic characteristics, viscosity and pH. During this period, it was also evaluated the spreadability according with the area obtained in relation to the weight applied. Antioxidant capacity and in vitro SPF determinations were also performed on formulations by the methods previously mentioned. The results show that the plant had good antioxidant activity , which can be related to the presence of flavonoids (24.67 mg/g) , polyphenols (33.90 mg/g) and condensed tannins (27.30 mg/g) and the amount of rutin (37.25 mg/g) and quercetin (6.09 mg/g) found in this study, but SPF was low in the extract (1.89), and in the formulations (around 1.7). Gel samples showed a higher spreadability than the cream. All samples remained stable during the storage period, thus maintaining its physical and chemical characteristics.